1st International FibreNet Science for the Public Day: Book of Abstracts - Jurko, Lucija; Kurečič, Manja; Kargl, Rupert (2019)
First international conference in the scope of FibreNet project funded by European comission. The conference brings together international representatives from industry and academia to discuss opportunities and strengths related to bio-based fibre products. In three consecutive sessions, fifteen international PhD students will present their research results, guide you along the value-chain of fibre-based products and give you the opportunity to discuss the future of bio-based materials.
Keywords: biobased materials; mechanical properties; paper; packaging; dissemination of research results